Antioxidant and anticancer effects and bioavailability studies of the flavonoid baicalin and its oxidovanadium(IV) complex - Martínez Medina, Juan José (2016)
Based on the known antioxidant effect of flavonoids, baicalin (baic) found in roots of Scutellaria has been selected. Its coordination complex with the oxidovanadium(IV) cation, Na4[VO(baic)2].6H2O (VIVO(baic)), was synthesized at pH 9 in ethanol and characterized by physicochemical methods. Spectrophotometric studies at pH 9 showed a ligand: metal stoichiometry of 2:1. By vibrational spectroscopy a coordination mode through the cis 5-OH and 6-OH deprotonated groups is inferred. EPR spectroscopy shows an environment of four aryloxide (ArO−) groups in the equatorial plane of the V=O moiety, both in solution and in the solid complex. The antioxidant capacity against superoxide and peroxyl radicals of VIVO(baic) resulted greater than for baicalin and correlated with previous results obtained for other VOflavonoid complexes. The coordination mode produces delocalization of the electron density and the stabilization of the radical formed by interaction with external radicals. The complex and the ligand displayed no toxic (Artemia salina test) and no mutagenic (Ames test) effects. The complex improved the ability of the ligand to reduce cell viability of human lung cancer cell lines (A549) generating reactive oxygen species (ROS) in cells, being this effect reversed by pre-incubation of the cells with antioxidants such as vitamins C and E. The addition of NAC (N-acetyl-L-cysteine, a sequestering agent of free radicals) suppresses the anticancer effect, confirming the oxidative stress mechanism. The complex interacted with bovine serum albumin (BSA) with stronger binding than baicalin and the mechanisms involved H bonding and van der Waals interactions.